Allosteric regulation of the P2X4 receptor channel pore dilation - Zemkova, Hana; Khadra, Anmar; Rokic, Milos B; Tvrdonova, Vendula; Sherman, Arthur; Stojilkovic, Stanko S (Pflugers Archiv, 2015)
Allosteric modulators of ligand-gated receptor channels induce conformational changes of the entire protein that alter potencies and efficacies for orthosteric ligands, expressed as the half maximal effective concentration (EC50) and maximum current amplitude, respectively. Here, we studied the influence of allostery on channel pore dilation, an issue not previously addressed. Experiments were done using the rat P2X4 receptor expressed in human embryonic kidney 293T cells and gated by adenosine 5'-triphosphate (ATP) in the presence and absence of ivermectin (IVM), an established positive allosteric regulator of this channel. In the absence of IVM, this channel activates and deactivates rapidly, does not show transition from open to dilated states, desensitizes completely with a moderate rate, and recovers only fractionally during washout. IVM treatment increases the efficacy of ATP to activate the channel and slows receptor desensitization during sustained ATP application and receptor deactivation after ATP washout. The rescue of the receptor from desensitization temporally coincides with pore dilation, and the dilated channel can be reactivated after washout of ATP. Experiments with vestibular and transmembrane domain receptor mutants further established that IVM has distinct effects on opening and dilation of the channel pore, the first accounting for increased peak current amplitude and the latter correlating with changes in the EC50 and kinetics of receptor deactivation. The corresponding kinetic (Markov state) model indicates that the IVM-dependent transition from open to dilated state is coupled to receptor sensitization, which rescues the receptor from desensitization and subsequent internalization. Allosterically induced sensitization of P2X4R thus provides sustained signaling during prolonged and repetitive ATP stimulation.
Keywords: vazba proteinů; ivermektin; purinergní receptory P2X4; lidé; Allosteric Regulation; Receptors, Purinergic P2X4; gating iontového kanálu; Ion Channel Gating; Protein Binding; krysa rodu Rattus; Ivermectin; alosterická regulace; Kinetics; Humans; kinetika; Protein Structure, Tertiary; HEK293 buňky; zvířata; Rats; Animals; HEK293 Cells; terciární struktura proteinů